2019
DOI: 10.3389/fncel.2019.00550
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DRP-1-Dependent Mitophagy Promotes Cochlea Hair Cell Senescence and Exacerbates Age-Related Hearing Loss

Abstract: Background: Mitochondrial dysfunction is considered to contribute to the development of age-related hearing loss (AHL). The regulation of mitochondrial function requires mitochondrial quality control, which includes mitophagy and dynamics. Dynamin-related Protein 1 (DRP-1) is believed to play a central role in this regulation. However, the underlying mechanism of DRP-1 in AHL remains unclear. Here, we examined whether the decline of DRP-1-dependent mitophagy contributes to the development of AHL. Methods: We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 22 publications
3
31
1
Order By: Relevance
“…Conversely, an activator of mitophagy, the mitochondrial membrane depolarizing agent CCCP [27], actually decreases the cisplatin-induced cytotoxicity which corroborates a previous report suggesting that autophagy suppresses ROS accumulation and oxidative stress in hair cells, thereby preventing cell death [28,29]. Induction of mitophagy mitigates aging-induced cardiovascular damages [30] in addition to promoting hair cell senescence and aggravating agerelated hearing loss [31]. Mitophagy could also lead to the failure of activation of apoptosis and induce resistance of cancer cells to chemotherapeutic treatment [32].…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, an activator of mitophagy, the mitochondrial membrane depolarizing agent CCCP [27], actually decreases the cisplatin-induced cytotoxicity which corroborates a previous report suggesting that autophagy suppresses ROS accumulation and oxidative stress in hair cells, thereby preventing cell death [28,29]. Induction of mitophagy mitigates aging-induced cardiovascular damages [30] in addition to promoting hair cell senescence and aggravating agerelated hearing loss [31]. Mitophagy could also lead to the failure of activation of apoptosis and induce resistance of cancer cells to chemotherapeutic treatment [32].…”
Section: Discussionsupporting
confidence: 87%
“…For instance, some authors have correlated the accumulation of aberrant mitochondria in senescent cells to insufficient turnover of mitochondrial population due to decreased mitophagic activity and lysosomal dysfunction [ 30 , 40 ]. Likewise, dysfunctional Dnm1l (dynamin 1 like, also known as Drp1)‐dependent mitophagy triggers senescence and contributes to age‐related hearing loss in mice [ 41 ]. Yet, in a model of 3D skin equivalents, pyruvate protected dermal fibroblasts from senescence by improving mitophagic activity and mitochondrial turnover [ 42 ].…”
Section: Mitochondria‐related Mechanisms Of Senescencementioning
confidence: 99%
“…Moreover, reduced mitophagy was observed in aged cochlea, which increased hearing loss [ 29 ]. This is supported by a study found that the inhibition of dynamin-related protein-1 (DRP-1), which initiates mitophagy, promotes cochlear hair cell senescence and exacerbates age-related hearing loss [ 30 ].…”
Section: Discussionmentioning
confidence: 95%